Hydrothermal Stability of Ru/SiO2–C: A Promising Catalyst for Biomass Processing through Liquid-Phase Reactions - Gatti, Martín (2017)
In this work, structural and morphological properties of SiO2–C composite material to be used as support for catalysts in the conversion of biomass-derived oxygenated hydrocarbons, such as glycerol, were investigated in liquid water under various temperatures conditions. The results show that this material does not lose surface area, and the hot liquid water does not generate changes in the structure. Neither change in relative concentrations of oxygen functional groups nor in Si/C ratio due to hydrothermal treatment was revealed by X-ray photoelectron spectroscopy (XPS) analysis. Raman analysis showed that the material is made of a disordered graphitic structure in an amorphous silica matrix, which remains stable after hydrothermal treatment. Results of the hydrogenolysis of glycerol using a Ru/SiO2–C catalyst indicate that the support gives more stability to the active phase than a Ru/SiO2 consisting of commercial silica.